Nursing Students Engagement in the Classroom and Clinical Practice: A Literature Review - Nina Indriyawati; Dwi Yuwono Puji Sugiharto; S. Martono; Muchsin Muchsin (Universitas Negeri Semarang, 2021)
Background: The engagement of nursing students is very important and can affect their progress and success in the nursing profession in the future. In nursing students their learning process is carried out in two environments, in the classroom and in the clinical practice, so that their engagement in both learning environments is very important to help students become more effective, current, and knowledgeable as they became engaged nursing dan become quality nurses. Purpose: The purpose of this research is to identify dan to explore the engagement of nursing students in the classroom and in clinical practice Methods: This study used a literature review design. This research used a database of indexed international journals such as Pubmed, Google Schoolar, Science Direct, and BMC for the period 2011-2021 to search for research articles. The keyword used was ‘Nursing Students, Students Engagement, Classroom, Clinical Practice’ and obtained 12 research articles. Research articles have been screened according to inclusion criteria of this research, namely the articles containing student engagement or the engagement of nursing students in the classroom or clinical practice. Results: Nursing students engagement in the learning process takes place in two environments, in the classroom and the clinical environment. Various studies on the engagement of nursing students showed a high level of engagement in the learning process that influenced by various factors including students, student with other students relationship, teachers, student-teacher/clinical instructors relationships, learning strategies, learning methods and student relationships with the learning environment. Conclusion: The engagement of nursing students is very important for their progress in the future profession, because the level of engagement will lead to various short-term and long-term learning outcomes. Engagement will affect the learning process of students in the classroom and develop academic skills in a clinical environment so that it will have an impact on student learning outcomes.